2021
DOI: 10.3390/ma14237384
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy Defects in Ga2O3: First-Principles Calculations of Electronic Structure

Abstract: First-principles density functional theory (DFT) is employed to study the electronic structure of oxygen and gallium vacancies in monoclinic bulk β-Ga2O3 crystals. Hybrid exchange–correlation functional B3LYP within the density functional theory and supercell approach were successfully used to simulate isolated point defects in β-Ga2O3. Based on the results of our calculations, we predict that an oxygen vacancy in β-Ga2O3 is a deep donor defect which cannot be an effective source of electrons and, thus, is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…Zacherle et al found the related phenomena. 143,169–171 Although V O s were easily formed at the low oxygen partial pressure, the transition level from the neutral state to the +2 state was the deep level in the bandgap whether in the O-rich or O-poor ambient condition, as shown in Fig. 10(c and d).…”
Section: Effects Of Defects and Impurities On Electronic Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Zacherle et al found the related phenomena. 143,169–171 Although V O s were easily formed at the low oxygen partial pressure, the transition level from the neutral state to the +2 state was the deep level in the bandgap whether in the O-rich or O-poor ambient condition, as shown in Fig. 10(c and d).…”
Section: Effects Of Defects and Impurities On Electronic Propertiesmentioning
confidence: 94%
“…, E c − E (0/+2) > 1 eV), which had also been obtained in other literature. 171–173 This indicated that the V O was a deep-level defect. Moreover, Onuma et al found that the blue emission was observed in β-Ga 2 O 3 , which was attributed to the recombination between the deep local donor and the trapped hole.…”
Section: Effects Of Defects and Impurities On Electronic Propertiesmentioning
confidence: 98%
“…Among five different phases of Ga 2 O 3 (α, β, γ, ε, and δ) [ 3 ], the orthorhombic β phase is the most stable thermodynamically, while the rhombohedral corundum α phase is semi-stable [ 4 ]. On the other hand, the band gap of α-Ga 2 O 3 is 5.3 eV [ 5 , 6 ], which is wider compared to β-Ga 2 O 3 4.9 eV [ 1 , 7 , 8 ], promising a higher breakdown field.…”
Section: Introductionmentioning
confidence: 99%
“…Opinions on the source of n-type conductivity are divided. The literature attributes it to unintentional dopants (introduced during the process of synthesis) as well as the presence of various types of defects in the crystal structure of this material: oxygen vacancies, hydrogen interstitials and substitutions, and Ga interstitials [2,15,16]. Experimental studies show that the resistivity of the crystalline grains' boundaries, but also their bulk, increases with the concentration of oxygen in the ambient atmosphere [17].…”
Section: Introductionmentioning
confidence: 99%